(untitled) (Journal of Bangladesh Academy of Sciences, 2011)
An efficient transformation protocol for tomato by reducing complexity and increasing transformation efficiency in four varieties namely, Bina tomato-3, Bina tomato-5, Bahar and Pusa Ruby. Transformation of cotyledonary leaf explant was performed with Agrobacterium tumefaciens strain LBA4404, harboring binary vector pBI121 having GUS and nptII marker genes. Frequency of transient GUS expression showed that the transformation competence in tomato was highly influenced by several factors, like optical density of Agrobacterium suspension, incubation period, co-cultivation period etc. In the present study, cotyledonary leaf explant from all four tested varieties found to be efficiently transformed by bacterial suspension having optical density (OD600) of 0.79 with 15 min incubation and 3 days of co-cultivation period. All these conditions along with pre-culture of explants prior to transformation gave better regeneration response following Agrobacterium infection. Moreover, for successful regeneration of transformed shoot 200 mg/l kanamycin was found to be most effective selection pressure. As all four varieties showed similar response the present protocol can be considered as a simple and genotype-independent reproducible protocol. Key words: Solanaceae; Transformation parameter; GUS expression; Cotyledonary leaf explant DOI: 10.3329/jbas.v34i2.6863 Journal of Bangladesh Academy of Sciences, Vol. 34, No. 2, 171-179, 2010